Design thinking a framework for applying design thinking in problem solving - Agarwal, Anuja (Cengage learning, 2023)
Design thinking a framework for applying design thinking in problem solving / Agarwal, Anuja. -- Delhi: Cengage learning, 2023 658.4063 Ag261 No. of Copies : 1